Diego de Pantoja, Past and Present of a Missionary Proposal - Sáez Palazón, Enrique (Razón y fe, 2020)
Diego de Pantoja’s forty-seven years of life are an example of dialogue and encounter between distant worlds. His intellectual formation and his pastoral intuition made possible some milestones that were difficult to repeat: he is the first Spaniard to set foot in the Forbidden City, the one who obtains the honours with license to bury Mateo Ricci in Chinese soil and the one who will face the challenge of defending a form of work and evangelical insertion that entailed respect for the culture of the host country. His refutatios and final memorials were a vain attempt to defend a missionary style.
Keywords: Diego de Pantoja; China; mission; Jesuits